Historical education levels and present-day non-cognitive skills - Eiji Yamamura (Osaka University, Institute of Social and Economic Research (ISER), 2015)
This study examined the extent to which education levels in the 19th century have shaped current norms, which influence individuals' present-day non-cognitive skills and perceptions of life. Cross-country, individual-level data were compared with each country's average years of schooling in 1870. After controlling for various country-level and individual characteristics, the key findings were as follows: (1) people in countries with high historical education levels place importance on hard work, ambition, and education; (2) people in countries with high historical education levels tend to show perseverance and have a sense of responsibility.
Keywords: I25; D83; Z13; N30; 330; historical education level; norms; non-cognitive skills